Implementasi Pembelajaran IPA di Masa Pandemi Covid-19 untuk Meningkatkan HOTS Siswa - Wibowo, Sri; Sukmayadi, Dodi; Winarni, Retno (Universitas Mathla'ul Anwar Banten, 2023)
The purposes of this research are (1) to describe online learning plans in science lessons to increase students' HOTS. (2) Describe the implementation of online learning in science lessons to increase student HOTS. (3) Describe the evaluation of online learning in science lessons to increase student HOTS. This study uses a qualitative approach. This research was conducted in class IX at SMP Negeri 3 Slogohimo, Wonogiri Regency in the odd semester of the 2021-2022 academic year. The subjects of this study were science teachers and some students in class IX at SMP Negeri 3 Slogohimo, Wonogiri Regency. The results of the study concluded that lesson planning in science lessons to increase students' HOTS was made by the teacher. Core activities based on: Indicators of achievement of GPA competencies, student characteristics, scientific approach, 4C (creativity, critical thinking, communication, collaboration), strengthening Character Education (PPK) and literacy. Planning closing activities includes reflection activities both individually and in groups, providing feedback, following up, informing activity plans for the next meeting, conducting assessments according to KD. The implementation of science learning in the context of increasing student HOTS is carried out through the application of learning models based on student activity, namely: discovery/inquiry learning models, Problem-based Learning (PBL) models, and Project-based Learnin models. The implementation of science learning to improve students' HOTS is constrained by the teacher's lack of understanding of the HOTS concept, so that learning carried out using inquiry, PBL, and project based learning models has not been able to improve higher-order thinking skills, meaning that new students have the ability to remember, understand, and apply, and have not been able to analyze, evaluate, and create. Evaluation of science lessons to increase student HOTS is carried out by teachers by utilizing information and ideas by changing their meanings and implications. The evaluation uses questions that are based on contextual problems, meaning that evaluation questions made by the teacher are related to situations faced by students on a daily basis, using a stimulus that stimulates students' thinking.